2016
DOI: 10.1007/s10549-016-4027-1
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of cathepsin S expression by HSP90 and 5-HT7 receptor-dependent serotonin signaling correlates with triple negativity of human breast cancer

Abstract: Our findings suggest CTSS as a candidate target for development of a strategy to inhibit breast cancer invasion, and indicate that HSP90 and 5-HT (regulators of CTSS) should be considered as alternative targets for the management of TNBC invasion and metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 32 publications
3
37
1
Order By: Relevance
“…Such concurrent inhibition of both CTSS and MMP-9 further indicates that BJ-2302 might act on a common signaling molecule that is involved in the regulation of both CTSS and MMP-9 expression. Previous reports have shown that the PI3K/Akt and Ras/Raf/ERK pathways merged at NF-κB activation, which regulates CTSS and MMP-9 expression 14,41 . In MDA-MB-231 cells, BJ-2302 significantly suppressed nuclear translocation of NF-κB (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Such concurrent inhibition of both CTSS and MMP-9 further indicates that BJ-2302 might act on a common signaling molecule that is involved in the regulation of both CTSS and MMP-9 expression. Previous reports have shown that the PI3K/Akt and Ras/Raf/ERK pathways merged at NF-κB activation, which regulates CTSS and MMP-9 expression 14,41 . In MDA-MB-231 cells, BJ-2302 significantly suppressed nuclear translocation of NF-κB (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Based on previous reports that MMPs 33,34 and cathepsins 14,35–38 are highly expressed in breast tumors, we investigated the relative contribution of the proteases in breast cancer cell invasion and metastasis in multiple breast cancer cell lines. Unlike hormone-responsive breast cancer cells (MCF-7 and T47D), TNBC cells (MDA-MB-231, HCC-1973, and Hs578T) expressed higher levels of both MMP-2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…10 In addition to its wellestablished role in cognition, 11 circadian rhythms 12 and depression, 13 its involvement in various cancers has also been reported. [14][15][16][17][18] Although the 5-HT 7 receptor has been implicated in many lung-associated pathologic processes in rats 19,20 and guinea-pigs, 21,22 research on the 5-HT 7 receptor in human lungs is limited. 23 In our study, an exploration of mRNA expression using bioinformatics analysis and the results of immunohistochemistry analysis both showed higher 5-HT 7 receptor expression levels in the tumor tissues of NSCLC than in adjacent normal tissues, which indicates that the 5-HT 7 receptor may play a role in the progression of NSCLC.…”
Section: Introductionmentioning
confidence: 99%